Evidence for population health - Heller, Richard F. (Oxford : Oxford University Press, 2005)
There is currently an urgent need for the public health community to develop its own evidence base as a tool for evaluating emerging interventions. This text provides the tools needed to facilitate this process.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health -- Evaluation; Evidence-based medicine; Health surveys